Navigating AI in Academia: Undergraduate Experiences with ChatGPT and the Redefinition of Academic Writing - Chatto, Meliza; Logronio , Ferlyn (Journal of Education and Learning Reviews, 2025)
Background and Aim: The integration of generative AI tools like ChatGPT into academic writing has generated both enthusiasm and ethical concern in higher education. While ChatGPT supports idea development, content organization, and revision, its use also raises issues related to plagiarism, authorship, and cognitive overreliance. Although prior research has examined the technical features and ethical risks of generative AI, few studies have explored students’ lived experiences. This study investigates how undergraduate students navigate the benefits and challenges of using ChatGPT in academic writing. Materials and Methods: A qualitative, theory-driven approach was adopted, drawing on the Technology Acceptance Model (TAM), academic integrity principles, and cognitive offloading theory. Fourteen undergraduate students engaged in thesis writing at a public state college in Region IX, Philippines, participated in semi-structured interviews and focus group discussions. Data were analyzed using Braun and Clarke’s thematic analysis. Trustworthiness was ensured through member checking, audit trails, and peer debriefing. Results: Thematic analysis revealed six key themes: (1) Academic Empowerment, highlighting ChatGPT’s role in enhancing productivity and confidence; (2) Ease and Accessibility, due to its intuitive interface and language flexibility; (3) Ethical Boundary Negotiation, with students adopting self-regulation strategies to avoid plagiarism; (4) Cognitive Trade-offs, reflecting concerns about reduced critical thinking and overdependence; (5) Peer and Policy Influence, shaped by unclear institutional guidelines and social norms; and (6) Technical Limitations, including vague responses, inconsistencies, and restrictions in the free version. Conclusion: Students perceive ChatGPT as a valuable tool in academic writing but express concern about ethical risks, cognitive dependence, and institutional ambiguity. The findings highlight the need for clear institutional guidelines, integration of AI literacy into the curriculum, and promotion of reflective, responsible use of generative AI in higher education.